Matilda - Dahl, Roald, 1916-1990.; Blake, Quentin (New York, N.Y. : Viking, 1988)
Matilda applies her untapped mental powers to rid the school of the evil, child-hating headmistress, Miss Trunchbull, and restore her nice teacher, Miss Honey, to financial security.
Elem. School Library Collection.
School Library Journal starred.
Wilson's Children.
5.2.
5.2
3-6
Keywords: Humorous stories; Schools -- Fiction; Humorous fiction; School stories